A synthetic process for lightening material for oil well cement
By combining modified diatomaceous earth and floating beads, combined with SiO2 aerogel wrapping and functional additives, the problems of easy leakage in low-pressure formations caused by high cement material density of oil wells and difficulty in construction of long-solid cement sections are solved, and the material density is reduced and the compressive strength is improved.
Patent Information
- Application Number
- CN202411797720.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-09
AI Technical Summary
In the prior art, the problems of high cement material density of oil wells are prone to leakage in low-pressure formations and difficulty in constructing long-solid cement sections.
A new lightweight material synthesis process for oil well cement is used to prepare composite lightweight materials by pretreating and aminating diatomaceous earth, mixing with modified drift beads, adding SiO2 aerogel to wrap and functional additives.
It significantly reduces the density of the material, improves its compressive strength and fluidity in complex well conditions, extends its service life, and enhances the construction efficiency and stability of oil well cement.
Smart Images

Figure GDA0005242597060000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oilfield chemistry, and in particular relates to a synthesis process of a lightening material for oil well cement. Background Art
[0002] With the continuous deepening of global oil exploration and development, the oil industry is facing more and more complex well conditions. In particular, the frequent appearance of low-pressure formations, weak formations and other formations prone to leakage has brought great difficulties to cementing operations. These complex conditions not only increase the difficulty of cementing, but also seriously affect the quality of cementing and the implementation of subsequent production increase operations. Therefore, low-density cement slurry systems came into being and gradually developed and improved to meet the needs of these complex well conditions.
[0003] Low-density cement slurry system is a technology that reduces the density of cement slurry by adding lightening materials. This system has significant advantages in cementing operations, especially in leaky formations. Due to the low formation pressure, traditional high-density cement slurry is prone to cause well leakage during injection, resulting in a decline in cementing quality, and in severe cases, may even cause safety accidents. Low-density cement slurry can significantly reduce injection pressure, reduce the risk of well leakage, and thus improve cementing quality.
[0004] However, with the continuous development and promotion of deep well and ultra-deep well technology, low-density cement slurry systems are also facing new challenges. In deep wells and ultra-deep wells, due to the complexity of formation pressure, temperature and other conditions, the problem of well leakage caused by leaky formations is more serious. This not only affects the cementing quality, but also increases the operating cost and time cost. Therefore, developing a new lightening material synthesis process for oil well cement to solve the technical problems of easy leakage in low-pressure formations and difficult cementing construction in long cementing sections caused by the high density of oil well cement materials in the existing technology, and improving its adaptability and performance under complex well conditions, has become an urgent problem to be solved in the current oil industry. Summary of the invention
[0005] The purpose of the present invention is to provide a novel synthesis process of lightening material for oil well cement, which is used to solve the technical problems of easy leakage in low-pressure formations and difficult cementing construction in long cementing sections caused by high density of oil well cement materials in the prior art.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention provides a novel synthesis process of a lightening material for oil well cement, comprising the following steps:
[0008] (1) pretreating and aminating diatomaceous earth to obtain modified diatomaceous earth;
[0009] (2) Modified floating beads are obtained by surface modification and SiO2 aerogel encapsulation of the floating beads; the modified diatomaceous earth is mixed with the modified floating beads to obtain a composite lightweight material;
[0010] (3) Dissolve methyl vinyl polyoxyethylene ether, sodium lauryl sulfate, hydroxypropyl methylcellulose and nano silicon dioxide in deionized water to prepare a premix, add the premix to the composite lightweight material, stir to make it uniformly dispersed, and obtain a novel lightening material for oil well cement.
[0011] Furthermore, in step (2), the mass ratio of modified diatomaceous earth to modified floating beads is 1-2:1; in step (3), the mass ratio of methyl olefin polyoxyethylene ether, sodium lauryl sulfate, hydroxypropyl methylcellulose, nano-silicon dioxide, composite lightweight material and deionized water is 0.3-0.5:0.5-1:0.1-0.3:1-2:30-40:20-30, methyl olefin polyoxyethylene ether is purchased from Hebei Shengchenglong Chemical Co., Ltd., sodium lauryl sulfate is purchased from Longhui Chemical, the stirring speed is 30-60rpm, and the time is 10-15min.
[0012] Furthermore, the preparation method of modified diatomite comprises the following steps:
[0013] S1, pretreatment: select high-purity diatomaceous earth for crushing and screening, put it into a high-temperature furnace for high-temperature calcination, and cool it to room temperature to obtain heat-treated diatomaceous earth;
[0014] S2, amination: weigh chitosan and put it into acetic acid solution, stir and dissolve it to prepare chitosan solution, immerse the heat-treated diatomaceous earth in the chitosan solution, stir and mix it, adjust the pH, and after the reaction is completed, obtain the amination diatomaceous earth liquid;
[0015] S3, post-treatment: filtering the aminated diatomite liquid with filter paper to obtain aminated diatomite, washing it with deionized water, placing the washed aminated diatomite in an oven for drying, and after drying, heating and curing it to obtain modified diatomite.
[0016] Furthermore, the particle size of the sieved diatomaceous earth in S1 is 60-200 mesh, the calcination temperature is 800-1000°C, and the calcination time is 2-4h; the deacetylation degree of chitosan in S2 is ≥80%, the concentration of the acetic acid solution is 1-2vt%, the concentration of the chitosan solution is 1-3wt%, the stirring temperature is 20-25°C, the stirring time is 1-2h, the pH is adjusted to 4-6 with acetic acid, the mass volume ratio of diatomaceous earth to chitosan solution is 1:10-50g / mL, the reaction temperature is 40-60°C, and the reaction time is 2-4h; S3 is washed with deionized water 3-5 times, the drying temperature is 60-65°C, the drying time is 32-48h, the curing temperature is 80-100°C, and the curing time is 2-4h.
[0017] Furthermore, the preparation method of the modified floating beads comprises the following steps:
[0018] Q1. Surface pretreatment: dissolve the surface pretreatment agent in deionized water to obtain a surface pretreatment solution, and immerse the floating beads in the surface pretreatment solution. After the surface pretreatment is completed, take out the floating beads, rinse them with deionized water, and dry them in an oven to obtain surface pretreated floating beads;
[0019] Q2, coupling treatment: dissolve the silane coupling agent in the solvent, stir well to obtain a coupling solution, immerse the surface pre-treated floating beads in the coupling solution, after the end, take out the surface pre-treated floating beads, rinse with ethanol, and dry them in an oven to obtain coupling treated floating beads;
[0020] Q3. Encapsulation: tetraethoxysilane, ethanol and water are mixed, a catalyst is added to obtain a tetraethoxysilane mixed solution, the mixture is stirred at room temperature to obtain a sol solution, the coupled treated floating beads are dispersed in the sol solution, and the solution is allowed to stand to obtain silica aerogel-encapsulated floating beads;
[0021] Q4, aging treatment: aging the silica aerogel-wrapped floating beads at room temperature to obtain aged gel-wrapped floating beads, immersing the aged gel-wrapped floating beads in ethanol for solvent replacement, and supercritically drying the replaced aged gel-wrapped floating beads to obtain dried aged gel-wrapped floating beads;
[0022] Q5. Surface modification: Soak the dried aged gel-coated floating beads in the surface pretreatment solution again for surface modification. After the modification, take out the aged gel-coated floating beads, rinse them with deionized water, and dry them in an oven to obtain modified floating beads.
[0023] Furthermore, the surface pretreatment agent in Q1 is a mixture of octylphenol polyoxyethylene ether and sodium silicate, the mass ratio of octylphenol polyoxyethylene ether and sodium silicate is 1:1, the concentration of the surface pretreatment solution is 1-5wt%, the immersion time is 2-3h, the drying temperature is 60-65°C, and the drying time is 2-4h; the silane coupling agent in Q2 is a mixture of KH550 and KH560, the mass ratio of KH550 and KH560 is 3-4:1, the solvent is a mixed solution of ethanol and deionized water, the volume ratio of ethanol and deionized water is 1:1, the concentration of the silane coupling solution is 2-3wt%, the immersion time is 2-3h, and the drying temperature is 80-8 5℃, drying time is 2-4h; the dosage ratio of tetraethoxysilane, ethanol and water in Q3 is 1-1.2g:1.5-2mL:1-1.2mL, the catalyst is 0.1M hydrochloric acid solution, the volume ratio of tetraethoxysilane mixture and catalyst is 100:0.8-2, the stirring time is 4-6h, the mass volume ratio of coupling treatment beads and sol solution is 1:5-10g / mL, standing for 22-24h, the aging time in Q4 is 48-50h, the aged gel-wrapped beads are immersed in ethanol 3-5 times, carbon dioxide is used for supercritical drying, the temperature is 31.1℃, the pressure is 7.38MPa, and the drying time is 24-28h.
[0024] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0025] 1. The present invention significantly reduces the density of the lightening material through the composite of modified diatomaceous earth and floating beads, meets the lightweight demand of oil well cement lightening treatment, SiO2 aerogel encapsulation and amino treatment significantly improve the mechanical strength and durability of the composite material, the addition of functional additives improves the fluidity and working performance of cement slurry, improves construction efficiency, hydroxypropyl methylcellulose and nano-silicon dioxide enhance the adhesion and durability of cement slurry, and prolongs the service life. Therefore, through this synthesis process, the new lightening material for oil well cement not only significantly reduces the density, but also greatly improves the compressive strength and fluidity.
[0026] 2. The present invention can remove organic impurities in diatomite, improve its pore structure, improve its thermal stability and chemical stability, and make the hydroxyl groups on the surface of diatomite more active, which is conducive to the subsequent amination reaction; chitosan is a natural polymer, which not only has good compatibility and adsorption, but also has low cost and environmental sustainability. The drying and curing process enhances the chemical bonding between chitosan and diatomite, significantly improves the mechanical strength and durability of the material, and the curing process further optimizes the interface performance between diatomite and cement matrix, improves the stability and durability of the overall material, thereby improving the compressive strength and long-term stability of oil well cement in harsh oil well environments.
[0027] 3. The present invention makes the surface of the floating beads hydrophilic by using octylphenol polyoxyethylene ether, thereby improving the dispersibility and stability of the floating beads in an aqueous environment and avoiding agglomeration. Sodium silicate provides siloxane bonds to enhance the silylation of the surface of the floating beads. The siloxane bonds of the silane coupling agents KH550 and KH560 are combined with the siloxy groups on the surface of the floating beads to form chemical bonds on the surface of the floating beads. In addition, the epoxy groups provide good water resistance to enhance the weather resistance and stability of the floating beads. Tetraethoxysilane is further hydrolyzed to form siloxane, which is then polymerized to form silica aerogel. The silica aerogel wrapping significantly improves the mechanical strength and compressive resistance of the floating beads. In addition, supercritical drying avoids the destruction of the aerogel structure during the drying process, improves the high porosity and structural stability of the material, and finally modifies the surface of the dried aged gel-wrapped floating beads to further enhance the hydrophilicity and dispersibility of the surface of the floating beads, ensures that it has good dispersibility in cement slurry, improves the interface bonding between the floating beads and the cement matrix, and improves the overall strength and durability. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Embodiment 1:
[0030] This embodiment discloses a novel synthesis process of a lightening material for oil well cement, comprising the following steps:
[0031] (1) pretreating and aminating diatomaceous earth to obtain modified diatomaceous earth;
[0032] (2) Modified floating beads are obtained by surface modification and SiO2 aerogel encapsulation of floating beads; 2000 g of modified diatomaceous earth is mixed with 1000 g of modified floating beads to obtain a composite lightweight material;
[0033] (3) 30 g of methyl vinyl polyoxyethylene ether, 50 g of sodium lauryl sulfate, 10 g of hydroxypropyl methylcellulose and 100 g of nano-silicon dioxide were dissolved in 2000 mL of deionized water to prepare a premix, and the premix was added to 3000 g of the composite lightweight material and stirred at a speed of 30 rpm for 10 min to uniformly disperse the composite lightweight material to obtain a novel lightening material for oil well cement.
[0034] The preparation method of modified diatomite comprises the following steps:
[0035] S1, pretreatment: select high-purity diatomite for crushing and screening, the particle size of the screened diatomite is 60 mesh, put it into a high-temperature furnace for high-temperature calcination, the calcination temperature is 800°C, the calcination time is 2h, and cool to room temperature to obtain heat-treated diatomite;
[0036] S2, amination: weigh 100g of chitosan with a deacetylation degree of ≥80% and put it into 1000mL of 1vt% acetic acid solution, stir and dissolve it thoroughly at a stirring temperature of 20°C for 1h to prepare a chitosan solution, immerse 20g of heat-treated diatomaceous earth in the chitosan solution, stir and mix thoroughly, adjust the pH to 4 with acetic acid, and react for 2h to obtain an amination diatomaceous earth solution;
[0037] S3, post-treatment: filtering the aminated diatomite liquid with filter paper to obtain aminated diatomite, washing it with deionized water for 3-5 times, placing the washed aminated diatomite in an oven for drying at a temperature of 60° C. for 32 hours, and after drying, heating and curing at a temperature of 80° C. for 2 hours to obtain modified diatomite.
[0038] The preparation method of the modified floating beads comprises the following steps:
[0039] Q1. Surface pretreatment: Dissolve 5g of octylphenol polyoxyethylene ether and 5g of sodium silicate in 1000mL of deionized water to obtain a surface pretreatment solution, and soak the floating beads in the surface pretreatment solution for 2 hours. After the soaking, take out the floating beads, rinse them with deionized water, and dry them in an oven at a drying temperature of 60°C for 2 hours to obtain surface pretreated floating beads;
[0040] Q2, coupling treatment: dissolve 15g of silane coupling agent KH550 and 5g of silane coupling agent KH560 in 500mL of ethanol and 500mL of deionized water, stir well to obtain a coupling solution, soak the surface pretreated floating beads in the coupling solution for 2h. After the soaking, take out the surface pretreated floating beads, rinse them with ethanol, and dry them in an oven at 80°C for 2h to obtain coupling treated floating beads;
[0041] Q3, encapsulation: 10g tetraethoxysilane, 150mL ethanol and 100mL water were mixed, 2mL 0.1M hydrochloric acid solution was added to obtain a tetraethoxysilane mixed solution, and the mixture was stirred at room temperature for 4h to obtain a sol solution, 25g coupling-treated floating beads were dispersed in the sol solution, and the mixture was allowed to stand for 22h to obtain silica aerogel-encapsulated floating beads;
[0042] Q4, aging treatment: aging the silica aerogel-wrapped floating beads at room temperature for 48-50 hours to obtain aged gel-wrapped floating beads, soaking the aged gel-wrapped floating beads in ethanol for 3-5 times to replace the solvent, and supercritically drying the replaced aged gel-wrapped floating beads using carbon dioxide at a temperature of 31.1°C, a pressure of 7.38MPa, and a drying time of 24 hours to obtain dried aged gel-wrapped floating beads;
[0043] Q5. Surface modification: soak the dried aged gel-coated floating beads in the surface pretreatment solution again for surface modification. The soaking time is 2 hours. After the soaking, take out the aged gel-coated floating beads, rinse them with deionized water, and dry them in an oven at a drying temperature of 60°C for 2 hours to obtain modified floating beads.
[0044] Embodiment 2:
[0045] This embodiment discloses a novel synthesis process of a lightening material for oil well cement, comprising the following steps:
[0046] (1) pretreating and aminating diatomaceous earth to obtain modified diatomaceous earth;
[0047] (2) Modified floating beads are obtained by surface modification and SiO2 aerogel encapsulation of floating beads; 2000 g of modified diatomaceous earth is mixed with 2000 g of modified floating beads to obtain a composite lightweight material;
[0048] (3) 40 g of methyl vinyl polyoxyethylene ether, 80 g of sodium lauryl sulfate, 20 g of hydroxypropyl methylcellulose and 150 g of nano-silicon dioxide were dissolved in 2500 mL of deionized water to prepare a premix, which was added to 4000 g of the composite lightweight material and stirred at a speed of 50 rpm for 13 min to uniformly disperse the composite lightweight material to obtain a novel lightening material for oil well cement.
[0049] The preparation method of modified diatomite comprises the following steps:
[0050] S1, pretreatment: select high-purity diatomite for crushing and screening, the particle size of the screened diatomite is 100 mesh, put it into a high-temperature furnace for high-temperature calcination, the calcination temperature is 900°C, the calcination time is 3h, and cool to room temperature to obtain heat-treated diatomite;
[0051] S2, amination: weigh 200g of chitosan with a deacetylation degree of ≥80% and put it into 1000mL of 1-2vt% acetic acid solution, stir and dissolve it thoroughly at a stirring temperature of 23°C for 1.5h to prepare a chitosan solution, immerse 60g of heat-treated diatomaceous earth in the chitosan solution, stir and mix thoroughly, adjust the pH to 5 with acetic acid, and react for 3h to obtain an amination diatomaceous earth solution;
[0052] S3, post-treatment: filtering the aminated diatomite liquid with filter paper to obtain aminated diatomite, washing it with deionized water for 4 times, placing the washed aminated diatomite in an oven for drying at a temperature of 62° C. for 40 h, and after drying, heating and curing at a temperature of 90° C. for 3 h to obtain modified diatomite.
[0053] The preparation method of the modified floating beads comprises the following steps:
[0054] Q1. Surface pretreatment: Dissolve 10g of octylphenol polyoxyethylene ether and 10g of sodium silicate in 1000mL of deionized water to obtain a surface pretreatment solution, and soak the floating beads in the surface pretreatment solution for 2.5h. After the soaking, take out the floating beads, rinse them with deionized water, and dry them in an oven at a drying temperature of 63°C for 3h to obtain surface pretreated floating beads;
[0055] Q2, coupling treatment: 17.5g of silane coupling agent KH550 and 5.5g of silane coupling agent KH560 were dissolved in 500mL of ethanol and 500mL of deionized water, and the mixture was stirred thoroughly to obtain a coupling solution. The surface pretreated floating beads were immersed in the coupling solution for 2.53h. After the immersion, the surface pretreated floating beads were taken out, rinsed with ethanol, and dried in an oven at 83°C for 3h to obtain coupling treated floating beads.
[0056] Q3, encapsulation: 11g tetraethoxysilane, 180mL ethanol and 110mL water were mixed, 4mL 0.1M hydrochloric acid solution was added to obtain a tetraethoxysilane mixed solution, and the mixture was stirred at room temperature for 5h to obtain a sol solution, 40g coupling-treated floating beads were dispersed in the sol solution, and allowed to stand for 23h to obtain silica aerogel-encapsulated floating beads;
[0057] Q4, aging treatment: The silica aerogel-wrapped floating beads were aged at room temperature for 49 hours to obtain aged gel-wrapped floating beads, and the aged gel-wrapped floating beads were immersed in ethanol for 4 times to replace the solvent, and the replaced aged gel-wrapped floating beads were supercritically dried using carbon dioxide at a temperature of 31.1°C, a pressure of 7.38MPa, and a drying time of 26 hours to obtain dried aged gel-wrapped floating beads;
[0058] Q5. Surface modification: Soak the dried aged gel-coated floating beads in the surface pretreatment solution again for surface modification. The soaking time is 2.5 hours. After the soaking, take out the aged gel-coated floating beads, rinse them with deionized water, and dry them in an oven at a drying temperature of 62°C for 3 hours to obtain modified floating beads.
[0059] Embodiment 3:
[0060] This embodiment discloses a novel synthesis process of a lightening material for oil well cement, comprising the following steps:
[0061] (1) pretreating and aminating diatomaceous earth to obtain modified diatomaceous earth;
[0062] (2) Modified floating beads are obtained by surface modification and SiO2 aerogel encapsulation of floating beads; 2500 g of modified diatomaceous earth is mixed with 1500 g of modified floating beads to obtain a composite lightweight material;
[0063] (3) 50 g of methyl vinyl polyoxyethylene ether, 100 g of sodium lauryl sulfate, 30 g of hydroxypropyl methylcellulose and 200 g of nano-silicon dioxide were dissolved in 3000 mL of deionized water to prepare a premix, and the premix was added to 4000 g of the composite lightweight material and stirred at a speed of 60 rpm for 15 min to uniformly disperse the composite lightweight material to obtain a novel lightening material for oil well cement.
[0064] The preparation method of modified diatomite comprises the following steps:
[0065] S1, pretreatment: select high-purity diatomite for crushing and screening, the particle size of the screened diatomite is 60-200 mesh, put it into a high-temperature furnace for high-temperature calcination, the calcination temperature is 800-1000°C, the calcination time is 2-4h, and cool to room temperature to obtain heat-treated diatomite;
[0066] S2, amination: weigh 300g of chitosan with a deacetylation degree of ≥80% and put it into 1000mL of 2vt% acetic acid solution, stir and dissolve it thoroughly at a stirring temperature of 25°C for 2h to prepare a chitosan solution, immerse 100g of heat-treated diatomaceous earth in the chitosan solution, stir and mix thoroughly, adjust the pH to 6 with acetic acid, and react for 4h to obtain an amination diatomaceous earth solution;
[0067] S3, post-treatment: filtering the aminated diatomite liquid with filter paper to obtain aminated diatomite, washing it with deionized water for 5 times, placing the washed aminated diatomite in an oven for drying at a temperature of 65° C. for 48 h, and after drying, heating and curing at a temperature of 100° C. for 4 h to obtain modified diatomite.
[0068] The preparation method of the modified floating beads comprises the following steps:
[0069] Q1. Surface pretreatment: Dissolve 25g of octylphenol polyoxyethylene ether and 25g of sodium silicate in 1000mL of deionized water to obtain a surface pretreatment solution, and soak the floating beads in the surface pretreatment solution for 3 hours. After the soaking, take out the floating beads, rinse them with deionized water, and dry them in an oven at a drying temperature of 65°C for 4 hours to obtain surface pretreated floating beads;
[0070] Q2, coupling treatment: dissolve 15g of silane coupling agent KH550 and 5g of silane coupling agent KH560 in 500mL of ethanol and 500mL of deionized water, stir well to obtain a coupling solution, soak the surface pretreated floating beads in the coupling solution for 3h. After the soaking, take out the surface pretreated floating beads, rinse them with ethanol, and dry them in an oven at a drying temperature of 85°C for 4h to obtain coupling treated floating beads;
[0071] Q3, encapsulation: 12g tetraethoxysilane, 200mL ethanol and 120mL water were mixed, 6.4mL 0.1M hydrochloric acid solution was added to obtain a tetraethoxysilane mixed solution, and the mixture was stirred at room temperature for 6h to obtain a sol solution, 25-64g of coupling-treated floating beads were dispersed in the sol solution, and allowed to stand for 24h to obtain silica aerogel-encapsulated floating beads;
[0072] Q4, aging treatment: aging the silica aerogel-wrapped floating beads at room temperature for 48-50 hours to obtain aged gel-wrapped floating beads, soaking the aged gel-wrapped floating beads in ethanol for 3-5 times to replace the solvent, and supercritically drying the replaced aged gel-wrapped floating beads using carbon dioxide at a temperature of 31.1°C, a pressure of 7.38MPa, and a drying time of 28 hours to obtain dried aged gel-wrapped floating beads;
[0073] Q5. Surface modification: Soak the dried aged gel-coated floating beads in the surface pretreatment solution again for surface modification. The soaking time is 3 hours. After the soaking, take out the aged gel-coated floating beads, rinse them with deionized water, and dry them in an oven at a drying temperature of 65°C and a drying time of 4 hours to obtain modified floating beads.
[0074] Comparative Example 1:
[0075] Comparative Example 1 Compared with Example 3, in the preparation process of the novel lightening material for oil well cement in Comparative Example 1, modified diatomaceous earth is not added, and other conditions remain unchanged.
[0076] Comparative Example 2:
[0077] Comparative Example 2 Compared with Example 3, in the preparation process of the novel lightening material for oil well cement in Comparative Example 2, no modified floating beads are added, and other conditions remain unchanged.
[0078] Comparative Example 3:
[0079] Comparative Example 3 Compared with Example 3, in the preparation process of the novel lightening material for oil well cement in Comparative Example 3, sodium lauryl sulfate is not added, and other conditions remain unchanged.
[0080] Experimental example
[0081] The silicate cement was slowly added to the premixed solution prepared in Example 1-3 and Comparative Example 1-3, and stirred at a speed of 500-600 rpm for 10 min to ensure that the cement particles were evenly dispersed to prepare 1.6 g / cm 3 , 1.5g / cm 3 and 1.4 g / cm 3 Three different densities of new lightening material cement samples for oil well cement were used. According to the national standard GB / T19139-2012, the new lightening material cement samples for oil well cement prepared in Examples 1-3 and Comparative Examples 1-3 were tested for sedimentation stability and thickening time. The test results are shown in Table 1:
[0082] Table 1
[0083]
[0084] According to the test results in Table 1, the oil well cement prepared in Examples 1-3 of the present invention has good sedimentation stability and a shorter thickening time. By comparing Comparative Examples 1-3 with Examples 1-3, it can be seen that adding modified diatomaceous earth, modified floating beads and sodium dodecyl sulfate can enhance the sedimentation stability of oil well cement and shorten its thickening time.
[0085] According to ISO679:2009 standard, the density is 1.4g / cm 3 The new type of lightening material cement samples for oil well cement prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to 48h compressive strength test, and the test results are shown in Table 2:
[0086] Table 2
[0087] Group 48h compressive strength (MPa) Example 1 26.8 Example 2 27.1 Example 3 27.5 Comparative Example 1 20.6 Comparative Example 2 19.7 Comparative Example 3 21.4
[0088] According to the test results in Table 1, the oil well cement prepared in Examples 1-3 of the present invention has good compressive strength. By comparing Comparative Examples 1-3 with Examples 1-3, it can be seen that adding modified diatomaceous earth, modified floating beads and sodium dodecyl sulfate can enhance the compressive strength of oil well cement.
[0089] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0090] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A synthesis process of lightening material for oil well cement, characterized in that: The following steps are involved: (1) pretreating and aminating diatomaceous earth to obtain modified diatomaceous earth; (2) Modified floating beads are obtained by surface modification and SiO2 aerogel encapsulation of the floating beads; The modified diatomaceous earth and the modified floating beads are mixed to obtain a composite lightweight material; (3) dissolving methyl vinyl polyoxyethylene ether, sodium lauryl sulfate, hydroxypropyl methylcellulose and nano silicon dioxide in deionized water to prepare a premix, adding the premix to the composite lightweight material, stirring to uniformly disperse it, and obtaining a lightening material for oil well cement; The preparation method of modified diatomite comprises the following steps: S1, pretreatment: select high-purity diatomaceous earth for crushing and screening, put it into a high-temperature furnace for high-temperature calcination, and cool it to room temperature to obtain heat-treated diatomaceous earth; S2, amination: weigh chitosan and put it into acetic acid solution, stir and dissolve it to prepare chitosan solution, immerse the heat-treated diatomaceous earth in the chitosan solution, stir and mix it, adjust the pH, and after the reaction is completed, obtain the amination diatomaceous earth liquid; S3, post-treatment: filtering the aminated diatomite liquid with filter paper to obtain aminated diatomite, washing it with deionized water, placing the washed aminated diatomite in an oven for drying, and after drying, heating and curing it to obtain modified diatomite; The preparation method of the modified floating beads comprises the following steps: Q1. Surface pretreatment: dissolve the surface pretreatment agent in deionized water to obtain a surface pretreatment solution, and immerse the floating beads in the surface pretreatment solution. After the surface pretreatment is completed, take out the floating beads, rinse them with deionized water, and dry them in an oven to obtain surface pretreated floating beads; Q2, coupling treatment: dissolve the silane coupling agent in the solvent, stir well to obtain a coupling solution, immerse the surface pre-treated floating beads in the coupling solution, after the end, take out the surface pre-treated floating beads, rinse with ethanol, and dry them in an oven to obtain coupling treated floating beads; Q3. Encapsulation: tetraethoxysilane, ethanol and water are mixed, a catalyst is added to obtain a tetraethoxysilane mixed solution, the mixture is stirred at room temperature to obtain a sol solution, the coupled treated floating beads are dispersed in the sol solution, and the solution is allowed to stand to obtain silica aerogel-encapsulated floating beads; Q4, aging treatment: aging the silica aerogel-wrapped floating beads at room temperature to obtain aged gel-wrapped floating beads, immersing the aged gel-wrapped floating beads in ethanol for solvent replacement, and supercritically drying the replaced aged gel-wrapped floating beads to obtain dried aged gel-wrapped floating beads; Q5. Surface modification: Soak the dried aged gel-coated floating beads in the surface pretreatment solution again for surface modification. After the modification, take out the aged gel-coated floating beads, rinse them with deionized water, and dry them in an oven to obtain modified floating beads.
2. A synthesis process of lightening material for oil well cement according to claim 1, characterized in that: In step (2), the mass ratio of modified diatomaceous earth to modified floating beads is 1-2:1; in step (3), the mass ratio of methyl olefin polyoxyethylene ether, sodium lauryl sulfate, hydroxypropyl methylcellulose, nano-silicon dioxide, composite lightweight material and deionized water is 0.3-0.5:0.5-1:0.1-0.3:1-2:30-40:20-30, the stirring speed is 30-60rpm, and the time is 10-15min.
3. A synthesis process of lightening material for oil well cement according to claim 1, characterized in that: The particle size of the sieved diatomaceous earth in S1 is 60-200 mesh, the calcination temperature is 800-1000°C, and the calcination time is 2-4h.
4. A synthesis process of lightening material for oil well cement according to claim 1, characterized in that: The deacetylation degree of chitosan in S2 is ≥80%, the concentration of the acetic acid solution is 1-2vt%, the concentration of the chitosan solution is 1-3wt%, the stirring temperature is 20-25°C, the stirring time is 1-2h, the pH is adjusted to 4-6 with acetic acid, the mass volume ratio of diatomaceous earth to chitosan solution is 1:10-50g / mL, the reaction temperature is 40-60°C, and the reaction time is 2-4h.
5. The synthesis process of a lightening material for oil well cement according to claim 1, characterized in that: In S3, the product is washed with deionized water for 3-5 times, the drying temperature is 60-65°C, the drying time is 32-48 hours, the curing temperature is 80-100°C, and the curing time is 2-4 hours.
6. A synthesis process of lightening material for oil well cement according to claim 1, characterized in that: The surface pretreatment agent in Q1 is a mixture of octylphenol polyoxyethylene ether and sodium silicate, the mass ratio of octylphenol polyoxyethylene ether and sodium silicate is 1:1, the concentration of the surface pretreatment solution is 1-5wt%, the immersion time is 2-3h, the drying temperature is 60-65℃, and the drying time is 2-4h.
7. A synthesis process of lightening material for oil well cement according to claim 1, characterized in that: The silane coupling agent in Q2 is a mixture of KH550 and KH560, the mass ratio of KH550 and KH560 is 3-4:1, the solvent is a mixed solution of ethanol and deionized water, the volume ratio of ethanol and deionized water is 1:1, the concentration of the silane coupling solution is 2-3wt%, the immersion time is 2-3h, the drying temperature is 80-85℃, and the drying time is 2-4h.
8. The synthesis process of a lightening material for oil well cement according to claim 1, characterized in that: The dosage ratio of tetraethoxysilane, ethanol and water in Q3 is 1-1.2g:1.5-2mL:1-1.2mL, the catalyst is 0.1M hydrochloric acid solution, the volume ratio of tetraethoxysilane mixture and catalyst is 100:0.8-2, the stirring time is 4-6h, the mass volume ratio of coupling treated floating beads and sol solution is 1:5-10g / mL, and it is allowed to stand for 22-24h. The aging time in Q4 is 48-50h, the aged gel-wrapped floating beads are immersed in ethanol for 3-5 times, and carbon dioxide is used for supercritical drying, the temperature is 31.1℃, the pressure is 7.38MPa, and the drying time is 24-28h.
Citation Information
Patent Citations
Solid low-density cement paste lightening admixture and preparation method thereof
CN103131401A
Preparation and application of chitosan-polyvinyl alcohol grafted diatomite composite material
CN112892495A